Synthesis and physicochemical characterization of Mg-Al-flufenamate-layered double hydroxide - Sarijo S.H.; Jadam M.L.; Jubri Z. (Trans Tech Publications Ltd, 2023)
Aluminum compounds; Fourier transform infrared spectroscopy; Intercalation; Manufacture; Nanocomposites; Flufenamic acid; FT-IR spectrum; Hybrid nanocomposites; Layered double hydroxides; Nano-hybrid composites; Physico-chemical characterization; Resulting materials; Self-assembly technique; Magnesium compounds